2010
DOI: 10.1261/rna.2127910
|View full text |Cite
|
Sign up to set email alerts
|

The adaptive significance of unproductive alternative splicing in primates

Abstract: Alternative gene splicing is pervasive in metazoa, particularly in humans, where the majority of genes generate splice variant transcripts. Characterizing the biological significance of alternative transcripts is methodologically difficult since it is impractical to assess thousands of splice variants as to whether they actually encode proteins, whether these proteins are functional, or whether transcripts have a function independent of protein synthesis. Consequently, to elucidate the functional significance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Our comparison of human and chimpanzee splicing expands previous knowledge of AS species specificity (Calarco et al 2007;Skandalis et al 2010). Although the sequences of the evaluated genes GNAS and WT1 were highly conserved between human and chimpanzee, we found significant interspecies differences in spliceisoform ratios.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Our comparison of human and chimpanzee splicing expands previous knowledge of AS species specificity (Calarco et al 2007;Skandalis et al 2010). Although the sequences of the evaluated genes GNAS and WT1 were highly conserved between human and chimpanzee, we found significant interspecies differences in spliceisoform ratios.…”
Section: Discussionsupporting
confidence: 68%
“…However, for most alternative transcripts, and in particular for those of low abundance, it is not obvious. Moreover, their formation often lacks phylogenetic conservation (Skandalis et al 2010). Isolated cases indicate, however, that low abundance of an alternative transcript and seemingly missing conservation are not sufficient criteria to discard an identified alternative transcript as being nonfunctional.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the process of intronic APA itself may play roles in gene expression, but that the specific outcomes (which tend to vary for orthologous genes in the two species) are not as important. A similar proposal has been made for alternative splicing outcomes in primates [36]. Thus, although the alternative splicing of transcripts from the DNA polymerase beta locus in primates shows little conservation in terms of specific events, there is nonetheless extensive alternative splicing leading to unproductive transcript isoforms throughout the primate lineage.…”
Section: Discussionmentioning
confidence: 59%
“…Molecular analyses over subsequent decades have demonstrated that alternative splicing influences intracellular localization, protein stability, enzymatic activity, and posttranslational modification (27,28). However, alternative splicing variants are often divided into two classes: productive or functional, wherein splice variants have biological functions; and unproductive or aberrant, representing transcripts with no known functions (29)(30)(31). Studies also have shown that unproductive splicing events prevent mRNA translation (e.g., no-go, non-sense-mediated, and nonstop decay) (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%